Strokectomy and Extensive Cisternal CSF Drain for Acute Management of Malignant Middle Cerebral Artery Infarction: Technical Note and Case Series - Tartara, Fulvio; Colombo, Elena Virginia; Bongetta, Daniele; Pilloni, Giulia; Bortolotti, Carlo; Boeris, Davide; Zenga, Francesco; Giossi, Alessia; Ciccone, Alfonso; Sessa, Maria; Cenzato, Marco (Frontiers in Neurology, 2019)
Background and purpose: Ischemic stroke is a major cause of death and disability worldwide. Up to 10% of cases evolves to malignant MCA stroke and mortality rate reaches 80% despite maximal medical therapy. Early decompressive craniectomy is effective in reducing mortality and improving the functional outcome but is an extended and invasive surgical approach burdened with a significant complication rate. We report a surgical treatment based on partial strokectomy and basal cisterns opening with massive CSF drain. Materials and methods: We retrospectively collected 15 cases of massive middle cerebral artery stroke treated with strokectomy between 2010 and 2017: 9 males and 6 females, mean age 61.73 ± 9.5 y. The right side was affected in 66.7%. All patients show clinical deterioration despite standard medical therapy and indication for surgery was placed after collegiate evaluation by neurologists and neurosurgeons based on clinical and radiological data. Results: Surgical procedure was performed 24 to 96 hours after the stroke onset. All the 15 patients survived the intervention, one patient died 20 days after the admission for non surgery-related issues (massive lung embolism). Mean GCS and NIHSS upon discharge were 11.4 ± 1,5 (range 8-14) and 18.2 ± 3.7 (range 14-23) respectively. Mean mRS at 12 months was 3.6 ± 1.1 (range 2 – 6). Mortality at 12 months was Mean follow-up was 18.1 months (range 12-34). The outcome was evaluated as satisfactory (mRs≤ 3) in 8 patients (53.3%). Mortality at 1 year was 6,7%. No patients developed hydrocephalus and 1 presented seizures. According to mRs outcome evaluation (mRs≤3 vs mRs>3) no quantitative variable resulted significantly different between the two groups, whereas the concomitant use of iv rTPA significantly differed (P<0.05) Conclusion: Supratentorial strokectomy seems to be safe and could be a potential alternative to decompressive craniectomy for the acute management of malignant MCA stroke. Further discussion is needed on how to attain a low complication rate, avoidance of bone reconstruction procedure and reduced occurrence of hydrocephalus or seizures. A larger, prospective multicentric study will be necessary to validate this technical approach.